KEBIJAKAN PENDIDIKAN MULTIKULTURAL PADA PESERTA DIDIK NON-ISLAM DI SEKOLAH MUHAMMADIYAH KOTA KUPANG - Syahrul, Syahrul; Arifin, Arifin (Universitas Muhammadiyah Ponorogo, 2018)
The aims of this study were to analyze multicultural educational policy for non-Islamic students at Kupang Muhammadiyah School. The researce use qualitative method. Subject of research was determined of technic of purposive sampling such as school environement, curriculum, teacher/headmaster and students at SMA and SMK Muhammadiyah Kupang. Meanwhile, the data was collected through in-depth interview, observation, file note, and document. The research uses qualitative method in one circle to analyze data among collection, organization, reading/memo, description, classification, interpretation, and visualization. As a result, the study found multicultural educational policy at SMA and SMK Muhammadiyah Kupang can be showed on recognition of the rights of the students, namely: schools as ideology Islamic approve students from whole religions, non-Islamic female students are not required to wear the hijab, schools provide religion teacher for each religion, and dismissing students on every religious holiday. On the other hand, multicultural education policy at SMA and SMK Muhammadiyah Kupang can be categorized into hidden curriculum, because it was not found multicultural word in curriculum even vision and mission, but multicultural values are supported by the teacher and headmaster.